Leaving the church: A note on the 1843 disruption of the Church of Scotland - Joseph Paul; John W. Sawkins (Heriot-Watt University, Department of Accountancy, Economics, and Finance, 2024)
This paper analyses the decisions made by ministers of the Church of Scotland regarding whether to leave and join the Free Church, or remain within the establishment, at the time of the 1843 Disruption. Using a newly constructed dataset drawn from a range of hitherto unconnected sources, it models the binary, stay or leave, decision through a linear probability model. The empirical results affirm the importance of age, type of church served and geographical context in explaining the overall pattern of secession. In addition they cast doubt on theories offering explanations which elevate the role of narrow economic concerns in driving the decision; explanations focusing on the impact of loss of stipend or family circumstances.
Keywords: C21; N33; N93; Z12; 330; Church; Scotland; 1843; Linear Probability Model